Implementing Metadata that Guide Digital Preservation Services - Angela Dappert; Adam Farquhar (International Journal of Digital Curation, 2011)
Effective digital preservation depends on a set of preservation services that work together to ensure that digital objects can be preserved for the long-term. These services need digital preservation metadata, in particular, descriptions of the properties that digital objects may have and descriptions of the requirements that guide digital preservation services. This paper analyzes how these services interact and use these metadata and develops a data dictionary to support them.